Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the expression [tex]\(\sqrt[4]{256 x^4 y^8}\)[/tex], we'll evaluate each component step-by-step. The fourth root of a product is equal to the product of the fourth roots of each factor.
Step 1: Evaluate the fourth root of the constant 256.
[tex]\[ \sqrt[4]{256} \][/tex]
256 is a power of 2:
[tex]\[ 256 = 2^8 \][/tex]
So:
[tex]\[ \sqrt[4]{256} = \sqrt[4]{2^8} \][/tex]
To find the fourth root, we divide the exponent by 4:
[tex]\[ \sqrt[4]{2^8} = 2^{8/4} = 2^2 = 4 \][/tex]
Step 2: Evaluate the fourth root of [tex]\(x^4\)[/tex].
[tex]\[ \sqrt[4]{x^4} \][/tex]
Similarly, we divide the exponent by 4:
[tex]\[ \sqrt[4]{x^4} = (x^4)^{1/4} = x^{4/4} = x^1 = x \][/tex]
Step 3: Evaluate the fourth root of [tex]\(y^8\)[/tex].
[tex]\[ \sqrt[4]{y^8} \][/tex]
Again, we divide the exponent by 4:
[tex]\[ \sqrt[4]{y^8} = (y^8)^{1/4} = y^{8/4} = y^2 \][/tex]
Step 4: Combine the results from Step 1, Step 2, and Step 3:
[tex]\[ \sqrt[4]{256 x^4 y^8} = \sqrt[4]{256} \cdot \sqrt[4]{x^4} \cdot \sqrt[4]{y^8} = 4 \cdot x \cdot y^2 \][/tex]
Thus, the simplified expression is:
[tex]\[ \sqrt[4]{256 x^4 y^8} = 4xy^2 \][/tex]
Step 1: Evaluate the fourth root of the constant 256.
[tex]\[ \sqrt[4]{256} \][/tex]
256 is a power of 2:
[tex]\[ 256 = 2^8 \][/tex]
So:
[tex]\[ \sqrt[4]{256} = \sqrt[4]{2^8} \][/tex]
To find the fourth root, we divide the exponent by 4:
[tex]\[ \sqrt[4]{2^8} = 2^{8/4} = 2^2 = 4 \][/tex]
Step 2: Evaluate the fourth root of [tex]\(x^4\)[/tex].
[tex]\[ \sqrt[4]{x^4} \][/tex]
Similarly, we divide the exponent by 4:
[tex]\[ \sqrt[4]{x^4} = (x^4)^{1/4} = x^{4/4} = x^1 = x \][/tex]
Step 3: Evaluate the fourth root of [tex]\(y^8\)[/tex].
[tex]\[ \sqrt[4]{y^8} \][/tex]
Again, we divide the exponent by 4:
[tex]\[ \sqrt[4]{y^8} = (y^8)^{1/4} = y^{8/4} = y^2 \][/tex]
Step 4: Combine the results from Step 1, Step 2, and Step 3:
[tex]\[ \sqrt[4]{256 x^4 y^8} = \sqrt[4]{256} \cdot \sqrt[4]{x^4} \cdot \sqrt[4]{y^8} = 4 \cdot x \cdot y^2 \][/tex]
Thus, the simplified expression is:
[tex]\[ \sqrt[4]{256 x^4 y^8} = 4xy^2 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.